Selecting Competent Talent for Offshore Installation Manager (OIM) using Analytic Hierarchy Process (AHP) - Wan Zulkarnain Bin Wan Ismail (Universiti Sains Islam Malaysia, 2025)
Matric: 3202531 (FST)-Restricted until February 2028